Plexin-B2 controls the timing of differentiation and the motility of cerebellar granule neurons - Battum, Eljo van; Heitz-Marchaland, Celine; Zagar, Yvrick; Fouquet, Stéphane; Kuner, Rohini; Chédotal, Alain (eLife, 2021)
Plexin-B2 deletion leads to aberrant lamination of cerebellar granule neurons (CGNs) and Purkinje cells. Although in the cerebellum Plexin-B2 is only expressed by proliferating CGN precursors in the outer external granule layer (oEGL), its function in CGN development is still elusive. Here, we used 3D imaging, in vivo electroporation and live-imaging techniques to study CGN development in novel cerebellum-specific Plxnb2 conditional knockout mice. We show that proliferating CGNs in Plxnb2 mutants not only escape the oEGL and mix with newborn postmitotic CGNs. Furthermore, motility of mitotic precursors and early postmitotic CGNs is altered. Together, this leads to the formation of ectopic patches of CGNs at the cerebellar surface and an intermingling of normally time-stamped parallel fibers in the molecular layer (ML), and aberrant arborization of Purkinje cell dendrites. There results suggest that Plexin-B2 restricts CGN motility and might have a function in cytokinesis.
Gesehen am 12.08.2021